Abductor muscle function after anterolateral approach in patients with unilateral end-stage hip osteoarthritis undergoing total hip arthroplasty: A prospective study - Wongsak, Siwadol; Jarungvittayakon, Chavarat; Chulsomlee, Kulapat; Jaovisidha, Suphaneewan; Sa-ngasoongsong, Paphon (Frontiers in Surgery, 2023)
Background: Total hip arthroplasty (THA) is a successful procedure for treating end-stage hip osteoarthritis (OA). Regarding the surgical approach for THA, the anterolateral (AL) approach, which requires anterior hemimyotomy of the gluteus medius muscle, has shown a long-term favorable outcome. However, to date, complete information related to hip abductor muscle outcomes after the AL approach is unavailable. This study therefore aimed to evaluate the postoperative outcome of patients who undergo THA using the AL approach in terms of hip abductor muscle recovery, pain, function, and muscle healing status. Methods: Twenty patients diagnosed with unilateral end-stage hip OA underwent cementless THA with the AL approach. All patient procedures were performed by a single surgeon. Preoperative and postoperative data were collected at 2-week, 6-week, 3-month, and 6-month follow-up periods. Hip abductor muscle power was measured via handheld dynamometer. The healing of the musculotendinous repair was evaluated with magnetic resonance imaging at 9 months. Results: After THA, hip abductor muscle power in the operated hip significantly increased as early as 3 months post-procedure when compared with the preoperative value (p < 0.05). The other parameters—including pain score, Harris hip score, and WOMAC score—significantly improved as early as 2 weeks post-operation (p < 0.05). In all patients, MRI scans showed good healing of the muscle repair site without a gap in the gluteus medius muscle. However, three patients (15%) had some fibrosis and tendon swelling at the repair site. Conclusion: This study demonstrated that patients with end-stage hip OA could experience significantly improved hip abductor motor function as early as 3 months after undergoing THA with the AL approach. Moreover, despite patients experiencing anterior hemimyotomy of the gluteus medius muscle, no significant complications emerged at the muscle repair site in the AL approach.